Fire Ant Venom Alkaloids Inhibit Biofilm Formation - Danielle Bruno de Carvalho; Eduardo Gonçalves Paterson Fox; Diogo Gama dos Santos; Joab Sampaio de Sousa; Denise Maria Guimarães Freire; Fabio C. S. Nogueira; Gilberto B. Domont; Livia Vieira Araujo de Castilho; Ednildo de Alcântara Machado (Toxins, 2019)
Biofilm formation on exposed surfaces is a serious issue for the food industry and medical health facilities. There are many proposed strategies to delay, reduce, or even eliminate biofilm formation on surfaces. The present study focuses on the applicability of fire ant venom alkaloids (aka ‘solenopsins’, from Solenopsis invicta) tested on polystyrene and stainless steel surfaces relative to the adhesion and biofilm-formation by the bacterium Pseudomonas fluorescens. Conditioning with solenopsins demonstrates significant reduction of bacterial adhesion. Inhibition rates were 62.7% on polystyrene and 59.0% on stainless steel surfaces. In addition, solenopsins drastically reduced cell populations already growing on conditioned surfaces. Contrary to assumptions by previous authors, solenopsins tested negative for amphipathic properties, thus understanding the mechanisms behind the observed effects still relies on further investigation.